Artificial Immune Systems for Solving the Uncapacitated Single-Allocation p-Hub Median Problem - Nobrega, Gabriel L.; Tasso, Vinicius J.; Souza, Allan G.; Fernandez, Stephanie A.; Silva, Daniel G. (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC), 2018)
Optimization problems such as the Uncapacitated Single-Allocation p-Hub Median Problem represent good models for real network design issues, hence an increasing research interest has emerged. A good hub location reduces costs and improves the quality of delivered services on network-based systems. In this work, two artificial immune systems are employed in order to address the problem, where the numerical results indicate good quality of solutions.